Mutational Alterations of the Key cis Proline Residue That Cause Accumulation of Enzymatic Reaction Intermediates of DsbA, a Member of the Thioredoxin Superfamily - Kadokura, Hiroshi (American Society for Microbiology, 2005)
The DsbA-DsbB pathway introduces disulfide bonds into newly translocated proteins. Conversion of the conserved cis proline 151 of DsbA to several hydrophilic residues results in accumulation of mixed disulfides between DsbA and its dedicated oxidant, DsbB. However, only a proline-to-threonine change causes accumulation of mixed disulfides of DsbA with its substrates.